Nutritional profiling of Eurasian woodcock meat: chemical composition and myoglobin characterization. (17th May 2018) - Landi, Nicola; Ragucci, Sara; Di Giuseppe, Antonella MA; Russo, Rosita; Poerio, Elia; Severino, Valeria; Di Maro, Antimo
Abstract: BACKGROUND: Meat from birds is a rich source of proteins for the human diet. In this framework, Eurasian woodcock ( Scolopax rusticola L.), a medium–small wading bird hunted as game in many Eurasian countries, is considered one of the best meats for culinary purposes. Since the nutritional composition of Eurasian woodcock meat has not yet been reported, we decided to determine the nutritional profile of S. rusticola meat. RESULTS: Macronutrient components (proteins, lipids and fatty acids) were determined, as well as free and total amino acids, and compared with those of the common pheasant. Eurasian woodcock meat contains high levels of proteins and essential amino acids. The levels of unsaturated fatty acids represent a great contribution to the total lipid amount. Among polyunsaturated fatty acids, linoleic acid (C18:2, n‐6) is the major essential fatty acid. Finally, we report the characterization of myoglobin (Mb) from Eurasian woodcock. CONCLUSION: The data revealed that meat from this bird could be a good source of quality raw proteins because of its amino acid composition, and it had a low lipid content. On the other hand, Mb characterization might be of benefit to the meat industry, by providing useful information for the determination of species‐specific differences in meat from birds. © 2018 Society of Chemical Industry